Gasification performance of sawdust, pelletized sawdust and sub-bituminous coal in a downdraft gasifier - Fatin Zafirah, Mansur; Faizal, Che Ku Mohammad; Noor Asma Fazli, Abdul Samad; Atnaw, Samson Mekbib; Sahimel Azwal, Sulaiman (Springer Nature Switzerland, 2020)
The paper is an experimental study of the gasification process of sawdust (SW), sawdust pellet (SWP) and sub-bituminous coal (SBCoal) by using downdraft gasifier. The gasification was undertaken in a lab-scale fixed-bed gasifier operating under air as an oxidizing agent. The comparison on the raw biomass, treated biomass and coal was assessed in term of the product gas and gasification performance at a fixed condition of gasification temperature of 750 °C and equivalence ratio of 0.25. The gasification performance was tabulated in the form of calorific value of the syngas (HHVsyngas), gasification efficiency (XCGE) and carbon conversion efficiency (XC). It was denoted that SWP produces the highest H2 and the lowest CO2. Furthermore, SBCoal possesses the highest gasification performance among the three feedstocks. Besides, the influence of the temperature between SW, SWP and SBCoal was evaluated at the equivalence ratio of 0.25. The findings demonstrate that rising the temperature, H2 and CO for SW, SWP and SBCoal are increase. The volume of the CO2 is constant as the temperature increases. In contrast, the CH4 decreases with increase in the gasification temperature. As the gasification temperature increases, HHVsyngas and XCGE of SW and SWP are increasing; meanwhile, SBCoal shows the opposite results. Simultaneously with rising gasification temperature, the XC’s of the SW, SWP and SBCoal are increasing.